1976
DOI: 10.1017/s0033291700013763
|View full text |Cite
|
Sign up to set email alerts
|

The coincidence of schizophrenia and Parkinsonism: some neurochemical implications

Abstract: SynopsisThe hypothesis has recently been advanced that increased activity of central dopaminergic mechanisms underlies the symptomatology of the schizophrenias. The evidence that dopaminergic transmission in the corpus striatum is impaired in Parkinson's disease suggests that observations on the relationship between Parkinson's disease and schizophrenia may illuminate the pathophysiology of the latter disease. Four cases are reported in which an illness with schizophrenic features developed in the setting of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In addition, the unusually high degree of basal ganglia involvement in diseases which resemble schizophrenia, supports the association of Parkinsonism with schizophrenia (Bowman & Lewis, 1980). The presence of psychotic symptoms in conjuction with Parkinsonism has been cited extensively in the past (Fairweather, 1947;Hollister & Glazener, 1961;Crow et al, 1976). More than 60 years ago McCown and Cook (1928) described the mental status of Parkinsonian patients as "extremely difficult to distinguish from ordinary cases of paraphrenia."…”
Section: Negative Schizophrenia Of Parkinsonismmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the unusually high degree of basal ganglia involvement in diseases which resemble schizophrenia, supports the association of Parkinsonism with schizophrenia (Bowman & Lewis, 1980). The presence of psychotic symptoms in conjuction with Parkinsonism has been cited extensively in the past (Fairweather, 1947;Hollister & Glazener, 1961;Crow et al, 1976). More than 60 years ago McCown and Cook (1928) described the mental status of Parkinsonian patients as "extremely difficult to distinguish from ordinary cases of paraphrenia."…”
Section: Negative Schizophrenia Of Parkinsonismmentioning
confidence: 93%
“…In addition to the neurochemical profile of negative schizophrenia, which overlaps with that of Parkinsonism, the co-occurrence of both disorders in the same patient suggests that they are interrelated (Crow et al, 1976;Friedman & Lannon, 1989). In addition, the unusually high degree of basal ganglia involvement in diseases which resemble schizophrenia, supports the association of Parkinsonism with schizophrenia (Bowman & Lewis, 1980).…”
Section: Negative Schizophrenia Of Parkinsonismmentioning
confidence: 95%
See 1 more Smart Citation
“…Although several authors (Hale & Bellizzi, 1980;Crow & Johnstone, 1976) suggested that low potency neuroleptics might have a place in treating this group of patients, it became clear that all conventional neuroleptics led to an unacceptable worsening of motor symptoms (Murdock & Williamson, 1982;Scholz & Dichgans, 1985;Friedman et al, 1987;Wolk & Douglas, 1992;Greene et al, 1993). Even low doses of conventional drugs were found to be associated with a profound worsening of motor symptoms (Shaw et al, 1980).…”
Section: Conventional Neurolepticsmentioning
confidence: 99%
“…Another problem in the interpretation of this literature is that some patients may have suffered from secondary Parkinsonian syndromes which are now recognized as being associated with psychosis; diffuse Lewy body disease, post-encephalitic parkinsonism and cerebro-vascular disease, for example. Reviewing this evidence, modern authors have concluded that psychosis in untreated Parkinson's disease (PD) is very rare (Crow & Johnstone, 1976;Cummings, 1992).…”
Section: Introductionmentioning
confidence: 99%